The boundary of Larsen Basin on Tabarin Peninsula, Antarctica - del Valle, R.A. (2004)
The Larsen Basin is the depositional area including all the upper Mesozoic-lower Cenozoic sedimentary rocks on the continental shelf of the northern Antarctic Peninsula. The western boundary between the basin fill and the rocks forming its technical basement, is not exposed, and was defined on the basis of aeromagnetic data. On petrological grounds, the Mesozoic marine sedimentary rocks exposed on western Tabarin Peninsula, at the north-eastern extremity of the Antarctic Peninsula, are assigned to the lower part of the Aptian-Eocene regressive megasequence that forms the basin filling. These rocks are faulted against sediments of the Antarctic Peninsula magmatic arc, suggesting that post- depositional tectonic movements probably occurred. This compressional deformation is assigned to mid-Cretaceous times, when the Coniacian partial basin inversion was accompanied by westward-verging deformation at the western basin margin. Although the original extent of the basin cannot be discerned from these data, the lithostratigraphical evidence and geographical position of the basin sediments, together with terrestrial magnetic data, confirm that the Larsen Basin extends onto the southern part of Tabarin Peninsula, and indicate that the western limit of the basin is located northward of the previously proposed limit. © 2004 Asociación Geológica Argentina.